Chromium boride-containing chromium sintered body, and method for producing the same
A sintered body with high boron content and controlled grain size and phase ratio is developed to address particle generation issues during sputtering, achieving high strength and improved film yield.
Patent Information
- Application Number
- JP2023163572
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-08
AI Technical Summary
Sintered bodies containing chromium boride with high boron content tend to generate particles during sputtering, leading to low yields of chromium boride films, despite having high bending strength.
A sintered body with a boron content of 16 atom% or more, consisting of a crystalline phase with a chromium phase and a chromium boride phase, is developed. This sintered body has a relative density of 90% or more, an average grain size of 10 μm or less, and an area ratio of the chromium boride phase exceeding 40%, which suppresses particle generation during sputtering.
The sintered body effectively suppresses particle generation during sputtering, maintaining high strength and enabling the formation of chromium boride films with improved yield.
Smart Images

Figure 2025054506000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered body containing chromium boride and a method for producing the same. [Background technology]
[0002] Chromium boride films used in the manufacturing process of tools and semiconductor components are produced by a sputtering method using a sintered body containing chromium boride as a target. In order to suppress cracking during processing and sputtering, efforts have been made to increase the strength of sintered bodies used in sputtering. For example, Patent Document 1 discloses that in a sintered body with a boron content of 16 atom% or more, the strength of the sintered body is increased by setting the area of the chromium boride phase to 40% or less, and that the flexural strength is improved as the area ratio of the chromium boride phase decreases.
[0003] Furthermore, in recent years, there has been a demand for improved production yields of chromium boride films, particularly in the semiconductor industry, and suppression of particle generation during sputtering has become an issue. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2000-199055 A Summary of the Invention [Problem to be solved by the invention]
[0005] In a sintered body containing chromium boride with a boron content of 16 atom% or more, if the chromium boride phase is reduced, an unreacted boron phase that causes abnormal discharge during sputtering is generated, and the sintered body is likely to have a low density. Therefore, although the sintered body of Patent Document 1 has high bending strength, it is likely to generate a large number of particles during sputtering, and the yield of chromium boride film formation using this body was low.
[0006] An object of the present disclosure is to provide at least one of a sintered body containing chromium boride, which is capable of suppressing particle generation during sputtering without reducing the area of the chromium boride phase and has strength suitable for use as a sputtering target, and a method for producing the same. [Means for solving the problem]
[0007] The present inventors have investigated a sintered body containing chromium boride suitable as a sputtering target for forming a chromium boride film, the sintered body having a high boron content. As a result, they have found that by controlling the crystal grain size of the chromium boride phase, a sintered body suitable as a sputtering target having high strength and capable of suppressing particle generation can be obtained.
[0008] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A sintered body having a boron content of 16 atom% or more, consisting of a crystalline phase including a chromium phase and a chromium boride phase, having a relative density of 90% or more, and further having an average crystal grain size of 10 μm or less and an area ratio of more than 40% in the chromium boride phase. [2] The sintered body according to the above [1], wherein the average crystal grain size of the chromium phase is 150 μm or less. [3] The sintered body according to [1] or [2] above, having a chromium content of 33 atom% or more and 84 atom% or less, and a boron content of 16 atom% or more and 67 atom% or less. [4] The chromium boride phase is CrB, Cr 2 B, Cr 5 B 3 , Cr 3 B 4 ,CrB 2 and CrB 4 The sintered body according to any one of the above [1] to [3], wherein the phase is one or more selected from the group consisting of: [5] A method for producing a sintered body according to any one of the above [1] to [4], comprising a heat treatment step of pressurizing and sintering a raw material powder containing 70% by mass or more and 96% by mass or less of chromium and 4% by mass or more and 30% by mass or less of boron in an inert atmosphere at a temperature higher than 1250°C and not higher than 2000°C. [6] A sputtering target comprising the sintered body according to any one of [1] to [4] above. [7] A method for forming a chromium boride film, comprising using the sintered body according to any one of [1] to [4] above. Effect of the Invention
[0009] The present disclosure can provide at least one of a film-forming material for a chromium boride film and a manufacturing method thereof, a sputtering target, and a manufacturing method for a chromium boride film, which are capable of forming a chromium boride film by a sputtering method without reducing the area of the chromium boride phase. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present disclosure will be described in detail below. However, the following description of the configuration elements is an example of an embodiment of the present disclosure, and the present disclosure is not limited to these contents. In addition, the configurations and parameters disclosed in this specification can be combined in any combination, and the upper and lower limits of the values disclosed in this specification can be combined in any combination. [Sintered body] The sintered body of this embodiment is a sintered body having a boron content of 16 atom% or more, consisting of a crystal phase including a chromium phase and a chromium boride phase, a relative density of 90% or more, and the chromium boride phase has an average crystal grain size of 10 μm or less and an area ratio of more than 40%. The sintered body of this embodiment can be used as a sputtering target (hereinafter, simply referred to as a "target") capable of producing a chromium boride film by a sputtering method.
[0011] The sintered body of the present embodiment is a sintered body containing at least chromium boride, and is preferably a sintered body containing chromium and chromium boride. Such a sintered body may be regarded as a so-called chromium sintered body containing chromium boride.
[0012] The crystal phase of the sintered body of this embodiment is composed of a chromium phase and a chromium boride phase. That is, the sintered body of this embodiment is a sintered body composed of a chromium phase and a chromium boride phase, and may be regarded as a sintered body composed of crystal grains of the chromium phase and crystal grains of the chromium boride phase. This suppresses the occurrence of abnormal discharge when used as a sputtering target.
[0013] Chromium boride phase is a compound of boron (B) and chromium (Cr) (Cr x B y ; where x and y are integers between 1 and 5, and CrB, Cr 2 B, Cr 5 B 3 , Cr 3 B 4 ,CrB 2 and CrB 4 Preferably, it is one or more selected from the group consisting of Cr 2 More preferably, it is B. The chromium phase is a phase consisting of chromium (Cr), and further consisting of metallic chromium.
[0014] The sintered body of the present embodiment contains a chromium phase and a chromium boride phase, which can be confirmed by the fact that it is composed of crystal grains of the chromium phase and crystal grains of the chromium boride phase. The crystal grains of the chromium phase and the crystal grains of the chromium boride phase constituting the sintered body of the present embodiment can be confirmed and distinguished by SEM-EDS measurement under the following conditions. That is, in the SEM-EDS measurement, crystal grains in which chromium (Cr) and boron (B) are detected can be regarded as crystal grains of the chromium boride phase, and crystal grains in which boron is not detected (crystal grains in which only chromium is detected) can be regarded as crystal grains of the chromium phase.
[0015] Accelerating voltage: 10kV Observation magnification: 50x In this embodiment, the SEM-EDS measurement may be performed using an SEM equipped with an EDS detector (for example, JSM-7900F, manufactured by JEOL Ltd.) The SEM-EDS measurement may be performed by observing the surface of the mirror-polished sintered body.
[0016] The average crystal grain size of the chromium phase is preferably 150 μm or less, 100 μm or less, or 50 μm or less. If the crystal grains of the chromium phase have such an average crystal grain size, the strength is high and the generation of particles during sputtering is further suppressed. The average crystal grain size of the chromium phase can be, for example, 0.5 μm or more, 1 μm or more, or 2 μm or more, and is preferably 0.5 μm or more to 150 μm or less, 1 μm or more to 100 μm or less, or 2 μm or more to 50 μm or less.
[0017] In this embodiment, the average crystal grain size of the chromium phase is the average of values (circle equivalent diameters) obtained by measuring the crystal grain size of the sintered body by a diameter method in which the longest part of the grain is the diameter of the crystal grains of the chromium phase observed in the SEM observation image obtained by the above-mentioned SEM-EDS measurement. The average crystal grain size of the chromium phase may be measured for 200±50 crystal grains of the chromium phase.
[0018] The average crystal grain size of the chromium boride phase is 10 μm or less, and preferably 8 μm or less or 5 μm or less. If the average crystal grain size of the chromium boride phase exceeds 10 μm, the strength of the sintered body is low, and the sintered body cracks during sputtering. The average crystal grain size can be 1 μm or more or 2 μm or more, for example, and is preferably 1 μm or more and 10 μm or less, or 2 μm or more and 5 μm or less.
[0019] In this embodiment, the average crystal grain size of the chromium boride phase may be obtained by analyzing an SEM observation image obtained by SEM-EBSD under the following conditions using an analysis program (e.g., Aztec Crystal). Specifically, the rotation angle (orientation difference (°) between measurement points) between adjacent measurement points by EBSD in the SEM observation image is measured, and a loop in which pixel boundaries with a rotation angle of more than 5° are continuous and closed without interruption is regarded as a crystal grain boundary, and the region within the loop is regarded as one crystal grain. The diameter (circle equivalent diameter) of a circle having an area equivalent to the area of the region constituting the crystal grain is regarded as the crystal grain size of the crystal grain of each chromium boride phase, and the arithmetic mean of 200±50 crystal grains may be calculated as the average crystal grain size. (Measurement conditions) Beam conditions: Acceleration voltage 20 kV, irradiation current 100 μA Working distance: 10mm (Programs used) Measurement program: AZtec Analysis program: AZtec Crystal
[0020] The area ratio of the chromium boride phase in the sintered body of this embodiment (hereinafter also simply referred to as "area ratio") is more than 40%, and preferably 45% or more or 50% or more. If the area ratio is less than 40%, abnormal discharge occurs during sputtering, and a large amount of particles is generated. The upper limit of the area ratio is arbitrary, but examples include 80% or less, 70% or less, or 60% or less, and it is preferably more than 40% and 80% or less, 45% or more and 70% or less, or 50% or more and 60% or less.
[0021] The area ratio is the percentage (%) excluding the area ratio of the region where boron is not detected, when the area of the entire EDS image obtained by the above-mentioned SEM-EDS measurement is taken as 100%.
[0022] The relative density of the sintered body of this embodiment is 90% or more, and preferably 95% or more or 97% or more. By having such a relative density, cracking of the sputtering target is further suppressed. The higher the relative density, the more preferable it is, but it can be 100% or less or less than 100%. The relative density is preferably 95% or more and 100% or less, or 97% or more and less than 100%.
[0023] In this embodiment, "relative density" refers to true density (d) [g / cm 3 ] versus bulk density (d') [g / cm 3 ] is the percentage [%] of the bulk density d' [g / cm 3 ] is the volume [cm ] measured by Archimedes' law 3 The true density is calculated from the mass (dry mass) [g] of the sintered body after drying in an air atmosphere at 60°C for 3 hours. 2 B, and the value is calculated from the following formula (A).
[0024] d=(a+b) / {(a / d Cr )+(b / d Cr2B )} (A) In the above formula, a is the mass of the chromium phase contained in the sintered body [g], b is the mass of the chromium boride phase contained in the sintered body [g]d Cr is the true density of chromium (7.19 g / cm 3 ) and d Cr2B is the true density of chromium boride (6.88 g / cm 3 The mass of the chromium phase and the chromium boride phase is calculated from the following formula, assuming that all the boron reacts with chromium to form the chromium boride phase. M Cr = A Cr -2×A B M Cr2B = A B a = M Cr ×52 / (M Cr ×52+M Cr2B ×114.8) b = M Cr2B ×114.8 / (M Cr ×52+MCr2B ×114.8)
[0025] In the above formula, A Cr is the amount of chromium (atom%), A B is the amount of boron (atom%), M Cr is the amount of chromium phase (mol%), M Cr2B is the amount of chromium boride phase (mol%), 52 is the atomic weight of chromium, and 114.8 is the amount of substance of the chromium boride phase.
[0026] The sintered body of this embodiment preferably has a composition in which the boron content is 16 atom% or more, more preferably the boron content is 16 atom% or more and 67 atom% or less, and the chromium content is 33 atom% or more and 84 atom% or less. If the boron content is 16 atom% or more, it is possible to form a chromium boride film by sputtering without using multiple sputtering targets. On the other hand, if the boron content is 67 atom% or less, it is possible to reduce particle generation during sputtering. The boron content is more preferably 16 atom% or more and 40 atom% or less, and even more preferably 18 atom% or more and 30 atom% or less. The chromium content is more preferably 60 atom% or more and 84 atom% or less, and even more preferably 70 atom% or more and 82 atom%.
[0027] In the sintered body of the present embodiment, the chromium content and the boron content are calculated from the following formula. Chromium content [atom%] = {(a / M a ) / (a / M a +b / M b )}×100 Boron content [atom%] = {(b / M b ) / (a / M a +b / M b )}×100
[0028] In the above formula, a is the mass of chromium contained in the sintered body [g], and b is the mass of boron contained in the sintered body [g]. ais the atomic weight of chromium = 52.0 [g / mol], M b is the atomic weight of boron = 10.8 [g / mol].
[0029] The sintered body of the present embodiment preferably has a composition in which chromium and boron make up 100% by mass, but may contain metal elements other than chromium and boron (hereinafter also referred to as "metal impurities") as long as the effect is achieved. Examples of metal impurities include one or more metal elements selected from the group consisting of silicon (Si), aluminum (Al) and iron (Fe) or compounds thereof. The total amount of metal impurities may be 5000 ppm by mass or less, 1000 ppm by mass or less, or 500 ppm by mass or less. Examples of the total amount of metal impurities include 0 ppm by mass or more, more than 0 ppm by mass, or 100 ppm by mass or more. In this case, the sintered body of the present embodiment may have a composition in which chromium, boron and metal impurities make up 100% by mass.
[0030] The chromium and boron in the sintered body of the present embodiment are the mass percentages (mass%) of chromium and boron relative to the mass of the sintered body obtained by mass measurement. The chromium and boron contained in the sintered body of the present embodiment may be measured by ICP analysis.
[0031] The amount of impurities in the sintered body of the present embodiment is the mass ratio (mass ppm) of the amount of impurities to the mass of the sintered body of the present embodiment obtained by mass measurement. The amount of impurities contained in the sintered body of the present embodiment may be measured by GDMS analysis.
[0032] Furthermore, the sintered body of this embodiment may contain oxygen to the extent that it does not deteriorate the properties when used as a sputtering target. The oxygen content is preferably 5000 mass ppm or less. If the oxygen content is 5000 mass ppm or less, particles derived from insulating oxides can be reduced. The oxygen content of the sintered body of this embodiment is preferably 1000 mass ppm or less or 500 mass ppm or less. Ideally, the sintered body of this embodiment does not contain oxygen (oxygen content is 0 mass ppm), but a realistic sintered body contains oxygen. Therefore, the lower limit of the oxygen content of the sintered body of this embodiment can be exemplified as more than 0 mass ppm or 100 mass ppm or more, and is preferably 100 mass ppm or more and 5000 mass ppm or less, or 200 mass ppm or more and 1000 mass ppm or less.
[0033] The oxygen content in the sintered body of this embodiment is the mass ratio of oxygen (ppm by mass) to the mass of the sintered body. The oxygen content in the sintered body of this embodiment can be measured by inert gas fusion-infrared absorption analysis. For the inert gas fusion-infrared absorption method, a general oxygen / nitrogen analyzer (e.g., LECO-ON736 oxygen / nitrogen analyzer) may be used.
[0034] In addition, depending on the measurement method, the total of the oxygen content and the contents of chromium, boron, and metal impurities in the sintered body of this embodiment does not necessarily have to be 100 mass %.
[0035] The sintered body of this embodiment may have any shape depending on the purpose, and may have, for example, one or more shapes selected from the group consisting of disk, cylinder, plate, rectangular parallelepiped, cube, polyhedron, and approximately polyhedron.
[0036] The flexural strength of the sintered body of this embodiment is preferably 250 MPa or more, more preferably 300 MPa or more or 400 MPa or more. As a result, when the sintered body of this embodiment is used as a target, the target is less likely to crack during sputtering. The higher the flexural strength, the more preferable it is, but the upper limit of the flexural strength of the sintered body of this embodiment can be 1000 MPa or less, 800 MPa or less, or 600 MPa or less, for example, and is preferably 250 MPa or more and 1000 MPa or less, or 300 MPa or more and 800 MPa or less.
[0037] The flexural strength of the sintered body of this embodiment may be measured by a method conforming to JIS R 1601. Test method: Three-point bending test Distance between fulcrums: 30mm Sample size: 3×4×40mm Head speed: 0.5mm / min [Sputtering target] The sintered body of the present embodiment can be used for known applications of sintered bodies, particularly chromium sintered bodies, but is preferably used as a sputtering target, and more preferably used as a sintered body for a sputtering target.
[0038] A sputtering target comprising the sintered body of this embodiment (hereinafter also referred to as "the target of this embodiment") may consist of the sintered body of this embodiment, or may be a target comprising a backing plate and the sintered body of this embodiment.
[0039] The target of this embodiment will be described below by taking as an example a sputtering target including a backing plate and the sintered body of this embodiment.
[0040] The backing plate may be made of any material that can conduct electricity and dissipate heat during sputtering, and examples of such materials include backing plates made of one or more materials selected from the group consisting of copper (Cu), aluminum (Al), titanium (Ti), and SUS.
[0041] In the target of this embodiment, the sintered body of this embodiment is bonded to a backing plate. The sintered body of this embodiment and the backing plate may be bonded directly or through a bonding material. The bonding material may be a known material, for example, indium (In).
[0042] The shape of the target of this embodiment may be any shape suitable for sputtering, and examples thereof include one or more shapes selected from the group consisting of a plate shape, a columnar shape, and a cylindrical shape.
[0043] In order to increase the deposition area, the area of the sputtering surface of the target in this embodiment is 200 cm 2 More than 350cm 2 or more than 800cm 2 The area of the sputtering surface is preferably 1500 cm or more. 2 or less than 1200cm 2 For example, the following can be used: 200 cm 2 More than 1500cm 2 Below, 350cm 2 More than 1200cm 2 It is preferable that: [Method of manufacturing sintered body]
[0044] The sintered body of this embodiment may be produced by any method as long as it satisfies the above-mentioned requirements. A preferred production method includes a heat treatment step of pressurizing and sintering a raw material powder containing 70% by mass or more and 96% by mass or less of chromium and 4% by mass or more and 30% by mass or less of boron in an inert atmosphere at a temperature higher than 1250°C and lower than 2000°C.
[0045] The raw powder may be at least one of a mixed powder of chromium powder and boron powder (hereinafter, also simply referred to as "mixed powder") and an alloy powder of chromium and chromium (hereinafter, also simply referred to as "alloy powder"), or may be a powder containing at least one of an alloy powder, chromium powder, and boron powder. For example, the mixed powder contains chromium powder in a ratio of 70 mass% to 96 mass% and boron powder in a ratio of 4 mass% to 30 mass%. The raw powder is obtained by mixing chromium powder and boron powder so that the total amount of the powder is 100 mass% (hereinafter, also referred to as "mixing process"). The alloy powder is obtained by heating the mixed powder to alloy it (hereinafter, also referred to as "alloying process").
[0046] The average particle size of the chromium powder may be 150 μm or less, or 100 μm or less, and may be 1 μm or more, or 3 μm or more.
[0047] The purity of the chromium powder is preferably 3N or more, or 4N or more. A preferred chromium source is metallic chromium. The purity of boron is preferably 2N or more, or 3N or more.
[0048] The average particle size of the boron powder may be 150 μm or less, or 100 μm or less, and may be 1 μm or more, or 3 μm or more.
[0049] The mixed powder preferably contains 90% by mass or more and 96% by mass or less of chromium powder, and more preferably 94% by mass or more and 95% by mass or less of chromium powder, and preferably contains 4% by mass or more and 10% by mass or less of boron powder, and more preferably 5% by mass or more and 6% by mass or less of boron powder.
[0050] The mixing method may be dry mixing, and may include one or more pulverizing methods selected from the group consisting of ball mill, jet mill, roll mill, disk mill, airflow pulverizing, and bead mill, with ball mill being preferred.
[0051] The alloy powder can be obtained by alloying the mixed powder, which can be performed by one or more methods selected from the group consisting of a melting method, a sintering method, a plating method, and a mechanical alloying method, with the melting method being preferred.
[0052] In the heat treatment step, at least one of the mixed powder and the alloy powder is pressure-sintered in an inert atmosphere at a temperature of more than 1250° C. This produces the sintered body of the present embodiment. The sintering method is pressure sintering, and specific examples of the pressure sintering include one or more selected from the group consisting of hot pressing, hot isostatic pressing (HIP) and discharge plasma sintering, with hot pressing being preferred.
[0053] The treatment temperature in the heat treatment step is more than 1250°C and not more than 2000°C. If the treatment temperature is 1250°C or less, the density of the sintered body decreases. If the treatment temperature is more than 2000°C, the strength of the sintered body decreases. Since the density of the obtained sintered body is likely to be improved, the treatment temperature is preferably 1300°C or more or 1350°C or more. The upper limit of the treatment temperature can be, for example, 1800°C or less, or less than 1600°C, and is preferably 1300°C or more and 1800°C or less, or 1350°C or more and less than 1600°C.
[0054] The upper limit of the pressure for the pressurized firing is, for example, 50 MPa or less or 40 MPa or less, and the lower limit is, for example, 10 MPa or more or 20 MPa or more, and preferably 10 MPa or more and 50 MPa or less, or 20 MPa or more and 40 MPa or less.
[0055] The heat treatment time may be appropriately adjusted depending on the performance of the heat treatment furnace, and may be, for example, from 1 hour to 10 hours.
[0056] The atmosphere in the heat treatment step may be an inert atmosphere, preferably one or more atmospheres selected from the group consisting of a nitrogen atmosphere, a helium atmosphere and an argon atmosphere, more preferably a helium atmosphere or an argon atmosphere.
[0057] The sintered body obtained by the above-mentioned heat treatment process may be used as the target of the present embodiment as it is, or may be processed to a desired size to be used as the target of the present embodiment. Also, the above-mentioned sintered body may be bonded to a backing plate to be used as the target of the present embodiment. EXAMPLES
[0058] The present disclosure will be described below with reference to examples. However, the present disclosure is not limited to these examples. (Relative Density) The relative density (%) of the sintered body was calculated according to JIS R 1634, as the bulk density (d') of the sintered body relative to the true density (d) of the sintered body, from the following formula:
[0059] Relative density [%] = (d' / d) x 100 Bulk density of sintered body d' [g / cm 3 ] is the volume [cm ] measured by Archimedes' law 3 ] and the dry mass [g] of the sintered body after drying in air at 60°C for 3 hours.
[0060] True density of sintered body d [g / cm 3 ] is the chromium boride phase Cr 2 B, and was calculated using the following formula (A). d=(a+b) / {(a / d Cr )+(b / d Cr2B )} (A)
[0061] In the above formula, a is the mass of chromium contained in the sintered body [g], b is the mass of chromium boride contained in the sintered body [g]d Cr is the true density of chromium (7.19 g / cm 3 ) and d Cr2B is the true density of chromium boride (6.88 g / cm 3 The masses of the chromium phase and the chromium boride phase were calculated from the following formula. M Cr = A Cr -2×A B M Cr2B = AB a= M Cr ×52 / (M Cr ×52+M Cr2B ×114.8) b = M Cr2B ×114.8 / (M Cr ×52+M Cr2B ×114.8)
[0062] In the above formula, A Cr is the amount of chromium (atom%), A B is the amount of boron (atom%), M Cr is the amount of chromium phase (mol%), M Cr2B is the amount of chromium boride phase (mol%), 52 is the atomic weight of chromium, and 114.8 is the amount of substance of the chromium boride phase. (Average grain size) <Cr phase>
[0063] The sintered body was mirror-polished and observed under the following conditions with a scanning electron microscope (SEM: manufactured by JEOL) to obtain an SEM image. The boron-undetected phase in the SEM image was regarded as the chromium phase, and the crystal grain size of the sintered body was measured by the diameter method, in which the longest part of the grain is taken as the diameter. At least three random points were observed, and 200±50 crystal grains were measured. Accelerating voltage: 10kV Observation magnification: 50x Chromium boride phase
[0064] The average grain size was measured using SEM-EBSD (SEM: JEOL, EBSD: Oxford Instruments) with the following measurement conditions and program, observing the target structure, and analyzing all observed grains using the analysis program (Aztec Crystal). Specifically, the rotation angle between adjacent measurement points by EBSD in the SEM image, i.e., the orientation difference (°) between the measurement points, was measured, and a continuous, uninterrupted closed loop of pixel boundaries with a rotation angle of more than 5° was considered to be a grain boundary, and the area within the loop was considered to be one grain. The diameter of a circle with an area equivalent to the area of the area that constitutes a grain was calculated as the grain size of the grain, and the arithmetic mean of all measured grains was calculated as the average grain size. (Measurement conditions) Beam conditions: Acceleration voltage 20 kV, irradiation current 100 μA Working distance: 10mm (Programs used) Measurement program: AZtec Analysis program: AZtec Crystal (area ratio)
[0065] The area ratio was calculated as the percentage (%) excluding the area ratio of the region where boron was not detected, when the area of the entire EDS image obtained by the above-mentioned SEM-EDS measurement was taken as 100%. (flexural strength) The flexural strength of the sintered body was measured under the following conditions by a method conforming to JIS R 1601. The measurement was carried out on two samples, and the average value was taken as the flexural strength. Test method: Three-point bending test Distance between fulcrums: 30mm Sample size: 3×4×40mm Head speed: 0.5mm / min (oxygen content)
[0066] The oxygen content of the sintered compacts was measured using an oxygen / nitrogen analyzer (TC436, manufactured by LECO). After grinding the surface of the sintered compacts to a thickness of 1 mm or more, rectangular column-shaped samples measuring 10 mm x 10 mm x 5 mm were cut out of the sintered compacts by incision and used as the measurement subjects. Measurement method: Impulse furnace melting - infrared absorption method (Metal impurity amount)
[0067] After grinding the surface of the sintered compact by 1 mm or more, a rectangular columnar sample of 10 mm x 10 mm x 5 mm was cut from the sintered compact by incision and used as the measurement subject. The amount of metal impurities was determined by measuring the content of each element in the sample. Measurement method: Glow discharge mass spectrometry (GDMS) Example 1
[0068] Chromium (Cr) powder (purity: 99.9%, particle size: 100 μm or less) was weighed out to be 95.1 mass % and boron (B) powder (purity: 99%, particle size: 45 μm or less) was weighed out to be 4.9 mass %. These powders were then dry mixed for 16 hours using a ball mill with nylon balls (diameter: 15 mm) to obtain a mixed powder.
[0069] The mixed powder was placed in a carbon mold (press die: diameter 15.2 cm) and sintered by hot pressing under the following conditions to obtain a disk-shaped sintered body of this example having a diameter of 15.2 cm and a thickness of 7 mm. Firing method: Hot press Heating rate: 200℃ / hour Firing atmosphere: Argon atmosphere Firing temperature: 1450℃ Firing pressure: 40MPa Baking time: 3 hours
[0070] The oxygen content of the sintered body of this example was 550 ppm by mass, and the metal impurity content was 146 ppm by mass (silicon content: 33 ppm by mass, aluminum content: 11 ppm by mass, iron content: 36 ppm by mass, magnesium content: 11 ppm by mass, sulfur content: 20 ppm by mass, manganese content: 11 ppm by mass, calcium content: 2 ppm by mass, titanium content: 4 ppm by mass, nickel content: 6 ppm by mass, gallium content: 3 ppm by mass, molybdenum content: 3 ppm by mass, tin content: 1 ppm by mass, other metal impurity content: 19 ppm by mass). Example 2
[0071] The chromium powder (purity: 99.9%, particle size: 100 μm or less) and the boron powder (purity: 99%, particle size: 45 μm or less) were weighed and mixed in a mortar so that the content was 90.6 mass%. The boron powder (purity: 99%, particle size: 45 μm or less) was 9.4 mass%. The powder was then heated in an argon atmosphere at 1450°C for 10 minutes to obtain an alloy powder.
[0072] These powders were weighed so that the chromium (Cr) powder was 47.5 mass% and the alloy powder was 52.5 mass%, and then dry-mixed for 16 hours in a ball mill using nylon balls (diameter 15 mm) to obtain a mixed powder.
[0073] The resulting mixed powder was sintered under the same conditions as in Example 1 to obtain a sintered body of this example. Example 3
[0074] Chromium powder (purity: 99.9%, particle size: 10 mm or less) was 95.1% by mass, and boron powder (purity: 99.5%, particle size: 3-7 mm) was 4.9% by mass. These powders were then weighed and mixed, and treated by gas atomization to obtain an alloy powder.
[0075] Except for using the obtained alloy powder, sintering was carried out under the same conditions as in Example 1 to obtain a sintered body of this example. Comparative Example 1
[0076] A sintered body of this comparative example was produced in the same manner as in Example 1, except that the firing conditions were as follows: Firing method: Hot press Heating rate: 200℃ / hour Atmosphere: Argon atmosphere Firing temperature: 1200℃ Pressure: 40MPa Baking time: 3 hours Comparative Example 2
[0077] Chromium powder (purity: 99.9%, particle size: 100 μm or less) was 90.6% by mass, and boron powder (purity: 99%, particle size: 45 μm or less) was 9.4% by mass. These powders were then weighed and mixed, and heated in an argon atmosphere at 1600°C for 10 minutes to obtain a Cr-B alloy powder.
[0078] Then, these powders were weighed so that the chromium (Cr) powder was 47.5 mass% and the Cr-B alloy powder was 52.5 mass%, and then dry-mixed for 16 hours using a ball mill with nylon balls (diameter 15 mm) to obtain a mixed powder.
[0079] The mixture was fired under the same conditions as in Example 1, except that the resulting mixed powder was used, to obtain a sintered body of this comparative example.
[0080] Table 1 shows the evaluation results of the sintered bodies obtained in the examples and comparative examples.
[0081] [Table 1]
[0082] It was confirmed that the sintered bodies of the examples all had a flexural strength of 250 MPa or more, and even 300 MPa or more, and had a strength that made them less susceptible to cracking during sputtering.
Claims
1. A sintered body containing chromium boride, the sintered body having a boron content of 16 atom% or more, consisting of a crystal phase including a chromium phase and a chromium boride phase, the relative density being 90% or more, and the chromium boride phase having an average crystal grain size of 10 μm or less and an area ratio of more than 40%.
2. 2. The sintered body according to claim 1, wherein the average crystal grain size of the chromium phase is 150 μm or less.
3. 3. The sintered body according to claim 1, wherein the chromium content is from 33 atom % to 84 atom %, and the boron content is from 16 atom % to 67 atom %.
4. The chromium boride phase is CrB, Cr 2 B, Cr 5 B 3 , Cr 3 B 4 , CrB 2 and CrB 4 3. The sintered body according to claim 1 or 2, which has one or more phases selected from the group consisting of:
5. 3. The method for producing a sintered body according to claim 1, further comprising a heat treatment step of pressurizing and sintering a raw material powder containing 70% by mass or more and 96% by mass or less of chromium and 4% by mass or more and 30% by mass or less of boron in an inert atmosphere at a temperature higher than 1250° C. and lower than 2000° C.
6. A sputtering target comprising the sintered body according to claim 1 or 2.
7. A method for forming a chromium boride film, comprising using the sintered body according to claim 1 or 2.
Citation Information
Patent Citations
Cr target material and its production
JP2000199055A